PATTERN OF PSYCHOTROPIC PRESCRIPTION IN A TERTIARY CARE TEACHING HOSPITAL: A CRITICAL ANALYSIS - HS, ROOPADEVI; KN, RAMESH; H, NAGABUSHAN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
objectives: (1) To study the prescription pattern of psychotropic drugs amongst patients attending the psychiatry outpatient department (OPD) in a tertiary care hospital, Mandya, (2) to evaluate patterns and recent trends in psychotropic polypharmacy. Methods: This was a prospective, cross-sectional and observational study, done over 8 weeks, among patients attending psychiatry OPD. The most recent prescribed psychopharmacological medication of the patients were collected in a standard proforma and analyzed according to World Health Organization (WHO) prescription indicators. Descriptive statistics such as frequency, percentage, mean, and standard deviation were used wherever appropriate. Results: A total of 405 prescriptions were evaluated. Anti-epileptics (22.9%), antidepressants (19.7%) and antipsychotics (11.0%) were the commonly advocated drug groups in more than half of prescriptions. Phenobarbitone (30.2%), escitalopram (27.9%), and risperidone (48.9%) were commonly used drugs among anti-epileptics, antidepressants, and antipsychotics, respectively. Nutraceuticals constituted 8.7% of total drugs. Percentage of drugs prescribed by generic name was 54.9%. Polypharmacy was prevalent in 2.7% of prescriptions. Percentage of drugs prescribed as fixed-dose combination was 21%. Conclusion: The WHO guidelines regarding prescription of drugs were followed consistently. The issue of prescribing by brand names need to be addressed. Polypharmacy was advocated for negligible number of subjects and the reasons were justifiable. Keywords: Prescription audit, Polypharmacy, Psychopharmacological agent.